Prison mental health: context is crucial: a sociological exploration of male prisoners' mental health and the provision of mental healthcare in a prison setting - Jordan, Melanie (2012)
This thesis represents a sociological exploration of Her Majesty’s Prison Service, male prisoners’ mental health, and the provision of National Health Service mental healthcare in a prison setting. This qualitative social science study is conducted in one prison establishment. The work is characterised as a policy and practice orientated exploratory case study. The study implements an inductive approach to the datum–theory relationship, a constructionist ontological position, and an interpretivist epistemological orientation. Semi-structured interviews are conducted in a male category B prison with healthcare centre staff (e.g. registered general nurse, registered mental health nurse, health care assistant, plus varied administration and clinical management staff), the secondary mental health team (psychologist, psychiatrist, community psychiatric nurse), prison governors, prison psychologists, primary-level mental health service users/prisoners, and secondary-level mental health service users/prisoners.